Penerapan Media Pembelajaran Augmented Reality untuk Meningkatkan Hasil Belajar Peserta Didik Kelas VII SMPN 33 Makassar - Nurlaili Nurlaili; Salma Samputri; Muhammad Aqil Rusli (Universitas Negeri Makassar, 2024)
This study aims to determine (1) the level of learning outcomes of students in grade VII SMP Negeri 33 Makassar before and after the application of augmented reality learning media 2) the improvement of learning outcomes of students in grade VII SMP Negeri 33 Makassar with the application of augmented reality learning media (3) a significant increase in learning outcomes of students in grade VII SMP Negeri 33 Makassar. This research is an experimental research with Pre-Experimental research design. The population in this study were all seventh grade students of SMPN 33 Makassar in the 2022/2023 school year as many as 290 students. Sampling using purposive sampling technique. This research instrument is in the form of multiple choice questions that contain cognitive levels of learning outcomes (C1-C4) as many as 25 items. Data collection is done by giving Pretest and Posttest. Data were analyzed with descriptive statistics and inferential statistics. The results of descriptive statistical analysis of pretest learner learning outcomes with an average score of 6.38 are in the low category and Posttest with an average score of 14.90 are in the medium category with. The increase in student learning outcomes with N-gain 0.46 is in the medium category. The results of inferential statistical analysis showed that there was a significant increase in student learning outcomes after the application of augmented reality learning media.